Changing Healthy Living Behavior in the Post-Pandemic Era: New Communication Culture - Putri, Kinkin Y. S.; Riadi, Yasir; Putri Suwito, Annisa (JURNAL KOMUNIKASI INDONESIA, 2024)
Changes in human life from 2019 to 2023 were reported to shift behavior, with an emphasis on well-being. In this context, the paradigm of healthy living is important, manifesting as a new cultural phenomenon. Therefore, this research was carried out to explore the transformation of post-pandemic healthy living behaviors into new cultural practices. The paradigms of health communication, healthy living attitudes, and new communication culture were also examined. Previous research supported the hypothesis and a quantitative approach was used by distributing questionnaires in several cities. Meanwhile, the validity and reliability tests of the variables enabled the continuation of the bivariate analysis. The results showed that there was a high influence of healthy living attitudes on the new post-pandemic communication culture. The descriptive results were positive in all indicators due to the strong influence of the bivariate analysis. Communication culture also had high dynamics and the concept was accompanied by changes in human life. As a result, future research could be developed from the perspective of theories and research methods used